2016
DOI: 10.1111/hel.12299
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and Antibiotic Resistance, A Continuing and Intractable Problem

Abstract: Helicobacter pylori, a human pathogen with a high global prevalence, is the causative pathogen for multiple gastrointestinal diseases, especially chronic gastritis, peptic ulcers, gastric mucosa-associated lymphoid tissue lymphoma, and gastric malignancies. Antibiotic therapies remain the mainstay for H. pylori eradication; however, this strategy is hampered by the emergence and spread of H. pylori antibiotic resistance. Exploring the mechanistic basis of this resistance is becoming one of the major research q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 121 publications
(224 reference statements)
3
122
1
3
Order By: Relevance
“…Owing to the antibiotic resistance and declining eradication rate of H. pylori in the clinic, more alternative therapeutic protocols are urgently necessary (20). In the present study, we aimed to investigate the anti-H. pylori activity and mechanism of PA.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the antibiotic resistance and declining eradication rate of H. pylori in the clinic, more alternative therapeutic protocols are urgently necessary (20). In the present study, we aimed to investigate the anti-H. pylori activity and mechanism of PA.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it is also linked to gastric adenocarcinoma (0.1%-3%) and gastric mucosa-associated lymphoid tissue (MALT) lymphoma (< 0.01%) in infected individuals[6-11]. H. pylori is defined as a Class I carcinogen by the World Health Organization and the International Agency for Research on Cancer[6,8,10]. In addition to gastrointestinal disorders, H. pylori also plays a role in extradigestive diseases, including immune thrombocytopenic purpura, unexplained iron deficiency anaemia, and vitamin B12 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Although the eradication rate achieved using this first-line regimen was reported to be around 90% in 2001, the rate decreased to less than 80% by 2014 [13,15] . The progressive increase in the incidence of CAM-resistant H. pylori strains is considered to be responsible for the decline in the eradication rate [16,17] . In this prospective randomized study, we compared the efficacy of EAM with that of EAC.…”
Section: Discussionmentioning
confidence: 99%
“…Although a multicenter study conducted in 2001 reported that the eradication rate using first-line therapy was around 90%, the rate decreased to 70-80% in 2014 [13,15] . A possible explanation for the decreased eradication rate is the prevalence of CAM-resistant H. pylori in Japan [16,17] . Okamura et al [16] reported that the rate of CAM resistance is above 30 and 50% in old and young patients, respectively.…”
mentioning
confidence: 99%